The organization of piano education in institutions of higher education of the PRC as an actual scientific and practical problem - Olena Druhanova; Zhang Jie (Scientific notes of the pedagogical department, 2023)
The purpose of the article is to analyze the topical issues of the organization of piano education in institutions of higher education in the scientific and pedagogical discourse of the People’s Republic of China at the end of the 20th - beginning of the 21st century. In the course of the study, it was established that the problem of organizing piano education in institutions of higher education, determining its prospects and further development strategies, is relevant and is constantly in the field of view of the scientific, pedagogical and musical public of the People’s Republic of China. In the list of issues that have been actively discussed in recent years, first of all, those related to the analysis of the achievements and achievements of piano education and the search for ways of its further improvement stand out. Among them were named: revision and improvement of scientific and methodical support of piano education; search for new approaches to training young performers; development of new curricula, programs of training courses and disciplines, various electives to deepen and expand the content of the training of applicants; search and implementation of new forms and methods of training performers; issues that are closely related to the establishment of abilites and the analysis of qualities that future entrants to conservatories and other types of higher education institutions providing piano education should possess. It has been proven that the problems and diﬃculties in the organization of piano education, which still exist, have been actively and widely discussed in the scientific-pedagogical and musical discourse of the People’s Republic of China. Issues related to the creation of a national Chinese piano school, integration of the piano into Chinese national culture, development and improvement of performance techniques, content, and quality become particularly acute of "priority tasks" that require an urgent solution, teaching piano, etc